Uji Efektivitas Ekstrak Daun Kratom (Mitragyna speciosa Korth) dalam Menekan Bakteri Ralstonia syzygii subsp. indonesiensis secara In Vitro - Awallia Puspita Sari; Yusriadi Marsuni (www.ulm.ac.id, 2026)
Bananas are a major horticultural commodity that makes a significant economic contribution in Indonesia. However, the productivity of this crop has declined drastically due to a blood disease infection caused by the banana. Blood Disease Bacterium (BDB). One type of pathogenic bacteria in the BDB group isRalstonia syzygii subsp. indonesian, which is known to be highly aggressive and easily spread. Efforts to control this disease generally rely on the use of synthetic bactericides, which risk environmental pollution and the development of pathogen resistance. Therefore, safer and more sustainable control alternatives are needed, such as the use of botanical pesticides from local plants. This study aims to evaluate the antibacterial activity of kratom leaf extract (Mitragyna speciosaKorth) on growthR. syzygii subsp. indonesianKratom leaf extract was obtained through a maceration method using 96% ethanol as a solvent, and antibacterial testing was conducted using agar diffusion techniques using paper discs. The extract concentrations tested included 5%, 10%, 15%, 20%, and 25%. The results showed that administration of kratom leaf extract (Mitragyna speciosa) at various concentrations is able to inhibit bacterial growthRalstonia syzygii subsp. indonesianin vitro. The average diameters of the inhibition zones observed for concentrations of 5%, 10%, 15%, 20%, and 25% were 4.15 mm; 6.71 mm; 7.75 mm; 8.39 mm; and 10.00 mm, respectively, while the control (0%) showed no antibacterial activity (0 mm). Further DMRT test results at the 5% level showed significant differences between treatments. This indicates that kratom leaf extract has potential as an antibacterial agent with the highest effectiveness obtained at a concentration of 25%.